EVALUASI EFEKTIVITAS PROGRAM FAT LOSS CHALLENGE TERHADAP PENURUNAN INDEKS MASSA TUBUH (BMI) PADA PEKERJA DI PT PUTRA PERKASA ABADI SITE MLP - Ashthofi Zainati; Fikri Fahmi Amrulloh; Syahrul Sumare; Sukardi Yusuf (BPPM Politeknik 'Aisyiyah Sumatera Barat, 2025)
Obesity is a significant health issue in the workplace and increases the risk of non-communicable diseases. In the mining sector, factors such as long working hours, shift patterns, stress, and limited access to healthy food contribute to this condition. This study aimed to evaluate the effectiveness of the Fat Loss Challenge Program implemented at PT Putra Perkasa Abadi (PPA) Site MLP in reducing workers’ Body Mass Index (BMI). Using a quasi-experimental one-group pretest–posttest design, 38 obese workers participated in a three-month intervention consisting of controlled healthy meals, daily physical activity, and regular monitoring. Paired t-test analysis showed a significant reduction in BMI (mean pre-test = 92.81; post-test = 88.08; p < 0.05). These results indicate that the program had a positive impact on participants’ BMI reduction. The success of the intervention was supported by integrated promotive, preventive, and curative strategies, including health education, initial screening, nutritional regulation, and habitual physical activity. The program is recommended as a model for occupational health interventions to reduce obesity in the mining industry.